Physico-chemical properties and surface characterization of renewable hybrid nanofilms interacting with model proteins. (February 2019) - Theodoratou, Antigoni; Costa, Luca; Bonnet, Laurent; Blanc, Christophe; Lapinte, Vincent; Etienne, Pascal; Milhiet, Pierre-Emmanuel; Robin, Jean-Jacques; Oberdisse, Julian; Chopineau, Joël; Aubert-Pouëssel, Anne
Graphical abstract: Highlights: The renewable nanofilms were found to have contact angles always below 90°, tunable Young modulus and hardness in the MPa range, as well as water vapour transmission rates which are increased by decreasing the silica ratio. Using a quartz crystal microbalance in energy dissipation mode and atomic force microscopy it was found that BSA and lysozyme form rigid layers on the surface with surface coverage close to 30%, and that both protein layers decrease their thickness after their dehydration. Cell culture experiments exhibited a good viability of the fibroblasts compared to ultra-low adhesion surfaces, which makes them potential candidates for biomedical applications. Abstract: A comprehensive characterization of physical-chemical properties and biological interactions of ca. 200-nm-thick hybrid films based on silylated (inorganic part) castor oil (organic part) is proposed. A series of such nanofilms was fabricated and cross-linked by a sol-gel procedure, and their properties such as hydrophilicity, hardness and water vapour transmission rate were systematically studied as a function of the ratio of silylated agent to castor oil. It was found that the nanofilms have contact angles always below 90°, tunable Young modulus and hardness in the MPa range. Moreover, their water vapour transmission rates are increased by decreasing the silica ratio. The protein adsorption and cytocompatibility were evaluated using model proteins and cells. The adsorption of the proteins bovine serum albumin (BSA) and lysozyme was characterized using a quartz crystal microbalance in energy dissipation mode (QCM-D), and atomic force microscopy (AFM). The combination of the latter provided evidence for the different affinities of the proteins with the films. It was found that BSA and lysozyme form rigid layers on the surface with surface coverage close to 30%, and that both protein layers decrease their thickness after their dehydration. Finally, cell culture experiments exhibited a good viability of the fibroblasts compared to ultra-low adhesion surfaces, which makes them potential candidates for biomedical applications.